DINAMIKA POLITIK MUSLIM TIONGHOA (STUDI KASUS PERSATUAN ISLAM TIONGHOA INDONESIA/PITI YOGYAKARTA) - gugun el guyanie (UIN Sunan Kalijaga Yogyakarta, 2019)
This reasearch attempts to reveals political movement of Muslim Tionghoa people (Islamic Chinese) at Yogyakarta. Today, there is a significant shifting of Muslim Tionghoa people. It can not be sparated from the latest problem commonly growing up at Indonesia. Actually, in many years ago, the Tionghoa people did political role at Indonesia, but untill now they often become a victime of ethnic violence. Moreover they are still discriminated politically. Their rights as citizen of Indonesia is not fulfilled. They are still distinguished with native people (pribumi), in Indonesia. Their political movement was still restricted so much, especially in Orde Baru era.However, recently, exactly after Reformation movement in 1998 occured, Tionghoa people in Indonesia are actively participating in political sphere. They are now success to be member of House of Representative, minister and governor. It is also done by Muslim Tionghoa in Yogyakarta. Muslim Tionghoa at Yogyakarta is united in a organization namely, PITI. PITI is a Muslim Tionghoa people organization existing in Indonesia. This organization has some branches in several Indonesian areas, including Yogyakarta.When early being established, PITI Yogyakarta moved in social and religious activities only. But today, PITI Yogyakarta is taking act in every areas including social, religion, culture, economy and politic. It is invented that the shifting movement of Muslim Tionghoa at Yogyakarta politically is related with ethnic discrimination in Indonesia. They would like to eliminate the such discrimination to reach their rights totally as Indonesian citizen.